230Th/U burial dating of ostrich eggshell. (1st September 2019) - Sharp, Warren D.; Tryon, Christian A.; Niespolo, Elizabeth M.; Fylstra, Nick D.; Tripathy-Lang, Alka; Faith, J. Tyler
Abstract: Obtaining precise and accurate dates for late Quaternary terrestrial sequences containing Middle Stone Age or Middle Paleolithic archaeological materials (ca. 30–300 ka) can be challenging. Many such sequences lie beyond the limit of radiocarbon dating (∼50 ka) and lack volcanic ashes suitable for 40 Ar/ 39 Ar dating. We report a dating approach with about ten times the range of radiocarbon dating (∼500 ka) based on a novel protocol for 230 Th/U dating of ostrich eggshell, a common component of African, Near Eastern and Asian archaeological sequences. Uranium in ostrich eggshell, typically at levels of tens to hundreds of ppb, is acquired after burial. However, accurate burial ages can be determined from measured 230 Th/U ages when corrected for uranium uptake via diffusion. Using ostrich eggshells from a Pleistocene-Holocene east African site, we have: (1) characterized the spatial distribution of uranium and common thorium ( 232 Th) concentrations in ostrich eggshell by laser ablation ICP-MS, (2) determined apparent 230 Th/U ages on outer and inner layers of eggshells by solution ICP-MS analyses of selectively abraded eggshells, and (3) calculated 230 Th/U burial ages using a simple model for diffusive uptake of uranium. We assess our method by comparing the 230 Th/U burial ages (median uncertainty 2.3%, 1 SD) with radiocarbon dates on carbonate from the same eggshells. We find good agreement in seven out of nine eggshells, confirming the accuracy of their 230 Th/U model ages. Eggshells that fail to yield reliable 230 Th/U ages may be recognized by anomalous patterns of apparent 230 Th/U ages, providing a reliability criterion innate to the 230 Th/U data. Ostrich eggshells are resistant to diagenesis simplifying 230 Th/U dating compared to bones and teeth. Eggshells of ostrich, emu, rhea and other living and extinct ratites found on six continents share similar structure and composition, suggesting our new approach to 230 Th/U dating of eggshell may be applicable in diverse late Quaternary terrestrial settings. Highlights: We develop and test a new method for U-series dating of ostrich eggshells. Modern and Pleistocene-Holocene archaeological ostrich eggshells were studied. Optimal dating material was identified using laser ablation profiles of 238 U and 232 Th. Most eggshells yielded accurate 230 Th/U ages when corrected for prolonged U uptake. Dating two fractions per eggshell aids identification of reliable 230 Th/U ages.